Creep Fatigue Analysis of a Nickel Superalloy over the Range 750-1040°C - de Abreu e Antunes, V. T. (Cranfield University, 1979)
After the review of the predictive methods in the high temperature fatigue field the characterization of the low cycle fatigue behaviour of a nickel superalloy, t4ARMOO2, is carried out using one of those predictive methods, the Strainranqe Partitioning method. The basic concepts and procedures of this method are reviewed and applied to NARt"O02 over the range 750° - 1040 C. -These'procedures invol ed the determination of the four basic life relationships at P50 C and 1040°C and their use in conjunction with a damage rule were then employed to assess the degree of insensitivity of the four basic strainrange versus life relationships to test temperature. Three damage rules and the assumptions behind them are discussed within the context of their application with the Stra i nrange Partitioning approach. An alternative analysis based on Ostergren's method is studied in a separate chapter and proved to be an easy and helpful method in predicting high temperature lot., cycle fatigue of several superalloys. The characterization of the creep-fatigue behaviour of 1,4F. RP"002 was completed by separation of initiation and propagation periods within two temperature intervals. A situation of earl formation of cracks at the higher temperature intervaa 950°- l040 C with accelerated growth. at lower tennperatures 750 - 250oC showed that great care is necessary when applying MAPP"002 isothermal results to cases where temperature varies.